[68Ga]Pentixafor-PET/CT for imaging of chemokine receptor CXCR4 expression in multiple myeloma - Comparison to [18F]FDG and laboratory values - Lapa, Constantin; Schreder, Martin; Schirbel, Andreas; Samnick, Samuel; Kortuem, Klaus Martin; Herrmann, Ken; Kropf, Saskia; Einsele, Herrmann; Buck, Andreas K.; Wester, Hans-Juergen; Knop, Stefan; Lueckerath, Katharina (Theranostics, 2017)
Chemokine (C-X-C motif) receptor 4 (CXCR4) is a key factor for tumor growth and metastasis in several types of human cancer including multiple myeloma (MM). Proof-of-concept of CXCR4-directed radionuclide therapy in MM has recently been reported. This study assessed the diagnostic performance of the CXCR4-directed radiotracer [68Ga]Pentixafor in MM and a potential role for stratifying patients to CXCR4-directed therapies. Thirty-five patients with MM underwent [68Ga]Pentixafor-PET/CT for evaluation of eligibility for endoradiotherapy. In 19/35 cases, [18F]FDG-PET/CT for correlation was available. Scans were compared on a patient and on a lesion basis. Tracer uptake was correlated with standard clinical parameters of disease activity. [68Ga]Pentixafor-PET detected CXCR4-positive disease in 23/35 subjects (66%). CXCR4-positivity at PET was independent from myeloma subtypes, cytogenetics or any serological parameters and turned out as a negative prognostic factor. In the 19 patients in whom a comparison to [18F]FDG was available, [68Ga]Pentixafor-PET detected more lesions in 4/19 (21%) subjects, [18F]FDG proved superior in 7/19 (37%). In the remaining 8/19 (42%) patients, both tracers detected an equal number of lesions. [18F]FDG-PET positivity correlated with [68Ga]Pentixafor-PET positivity (p=0.018). [68Ga]Pentixafor-PET provides further evidence that CXCR4 expression frequently occurs in advanced multiple myeloma, representing a negative prognostic factor and a potential target for myeloma specific treatment. However, selecting patients for CXCR4 directed therapies and prognostic stratification seem to be more relevant clinical applications for this novel imaging modality, rather than diagnostic imaging of myeloma.
CRIS-Team Scopus Importer:2023-03-23
Keywords: CXCR4; FDG; Molecular imaging; Multiple myeloma; PET; Radionuclide therapy; Theranostics